Structural incorporation of As5+ into rhomboclase ((H5O2)Fe3+(SO4)2·2H2O) and (H3O)Fe(SO4)2. (March 2016) - Bolanz, Ralph M.; Göttlicher, Jörg; Steininger, Ralph; Wieczorek, Arkadiusz
Abstract: Iron sulfates represent an essential sink for the toxic element arsenic in arid and semi-arid mining areas with high evaporation rates. Information about the structural incorporation of As 5+ in iron sulfates, however, remains scarce. Here we present evidence for the heterogeneous substitution of S 6+ by As 5+ in the crystal structure of rhomboclase ((H5 O2 )Fe 3+ (SO4 )2 ·2H2 O) and its dehydration product (H3 O)Fe(SO4 )2 . Rhomboclase (Rhc) was synthesized in the presence of As 5+ with molar As/Fe ratios of 0, 0.25, 0.5, 0.75 and 1.0, resulting in As loads of 0.0, 0.93, 1.44, 1.69 and 1.87 wt.%, respectively. The unit cell parameters of Rhc increase from 9.729(6), 18.303(2), and 5.432(1) Å for a, b, and c, to 9.745(9), 18.332(5), and 5.436(8) Å when Rhc is crystallized at a molar As/Fe ratio of 1. Simultaneously, the crystallite size decreased from 304 to 176 nm. In situ dehydration of Rhc to (H3 O)Fe(SO4 )2, investigated by powder X-ray diffraction, shows that Rhc starts to dehydrate at 76 °C, which is completed at 86 °C. The presence of As 5+ does not impact the start or end temperatures of Rhc dehydration but does accelerate the dehydration. X-ray absorption fine structure spectroscopy (EXAFS) reveals that S 6+, in the Rhc and (H3 O)Fe(SO4 )2 structure, is replaced by As 5+, while the polymerization of AsO4− tetrahedra and FeO6− octahedra during the formation of (H3 O)Fe(SO4 )2 results in a strong distortion of the AsO4− tetrahedron. Highlights: Rhomboclase can incorporate As 5+ by substitution of S 6+ . Incorporated As 5+ does not impact the dehydration temperature of rhomboclase. As 5+ remains within the (H3 O)Fe(SO4 )2 structure after rhomboclase dehydration. Polymerization of AsO4 and FeO6 in (H3 O)Fe(SO4 )2 leads to AsO4 distortion.